Digital planning and guided dual technique in esthetic crown lengthening: a randomized controlled clinical trial - Carrera, Thaisa Macedo Iunes; Freire, Alice Engel Naves; de Oliveira, Guilherme José Pimentel Lopes; dos Reis Nicolau, Sabrina; Pichotano, Elton Carlos [UNESP]; Junior, Noé Vital Ribeiro; Pires, Luana Carla; Pigossi, Suzane Cristina (Springer Nature, 2023)
Objectives: The present study aimed to compare the guided dual technique with the conventional technique in esthetic crown lengthening (ECL). Materials and methods: The trial registration number is NCT04922086. Twenty-four participants diagnosed with altered passive eruption (APE) type I subcategory B were selected and allocated into two groups. In the control group (n = 12), the ECL procedure was planned by clinical examination and transgingival probing; in the test group (n = 12), the ECL procedure was carried out using digital planning and a double guide. Clinical parameters were assessed at baseline, immediately after the intervention (IAI), and at 4, 8, and 12 months of follow-up. Results: The clinical crown length (CCL) mean at baseline was 8.09 mm (± 0.77) and increased significantly to 9.92 mm (± 0.62) IAI, with minimal significant reduction after 12 months (9.47 mm [± 0.60]) in the control group. Similarly, in the test group, the mean CCL at baseline was 8.04 mm (± 0.69) and increased significantly to 9.94 mm (± 0.57) IAI, with minimal reduction after 12 months (9.35 mm [± 0.80]). No differences were found between the mean CCL determined in the digital planning and after 12 months. No correlation was found between gingival thickness and gingival margin stability. High esthetic satisfaction was demonstrated by participants/specialists without differences between groups. Conclusions: In conclusion, the guided dual technique was as effective as the conventional technique for treatment of APE, with stable results after 12 months of follow-up. Clinical relevance: The guided dual technique aims to transfer both the gingival and bone resection planned position to facilitate the ECL surgical procedure and increase treatment predictability.
Keywords: Cone-beam computed tomography; Crown lengthening; Dental photography; Esthetics